A comparative radiographic study to evaluate bone density around titanium implants supporting zirconia crowns compared with zirconia crowns lined with PEEK material after one year of functional loading. - سليمان, بتول; نزيه عيسى,; تهامة يوسف, (Latakia University Journal -Medical Sciences Series, 2024)
Considering that changing the support over the implant affects the shape of the forces transmitted to the bone. The aim of this research was to study the effect of two different types of abutments on the integrity and health of the bone around them by comparing the bone density around titanium implants supporting zirconia restorations with zirconia restorations with a polyether ether ketone base manufactured by CAD/CAM. Within one year after functional loading. The research sample consisted of 28 titanium implants distributed among 14 patients who had the loss of one posterior tooth on each side according to the type of abutment: the posterior loss was compensated for with one titanium implant on each side of the same jaw, and after complete healing, that is, about three months after surgery, the prostheses placement. Radiological examinations of patients using cone beam computed tomography (CBCT) were performed before implantation and after 6-12 months of prosthesis and functional loading. A comparison was made between the bone densities around the implants on the patient's right and left sides. Bone density was measured around each implant in three apical-body-neck areas and arithmetic averages of density values were taken during the observation period. The data were analysed using the student test for the difference in means of values between two independent samples (Independent Samples Test) using the statistical program SPSS. The results showed that the sig value (0.161) is greater than the value of the significance level (0.05), and therefore we accept the null hypothesis that there are significant differences between the densities values. Recorded bone mass around implants according to the material used in the prosthesis. The results of this study, through CBCT images, showed a significant increase in bone density around titanium implants supporting zirconia prostheses with a layer of polyether ether ketone (PEEK), better than those loaded with traditional zirconia crowns, with statistically significant differences. Thus, it shows an advantage in using these fewer rigid materials and taking advantage of their advantages. To improve bone quality around implants